Efforts to enhance madrasah students’ academic achievement through the implementation of the tus method - Budi Utomo; Mudzakkir Ali; Ghufron Hamzah (Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the implementation of the Tutur Uwur Sembur (TUS) instructional method in enhancing student academic achievement at MIS Unggulan Masjid Besar Jabalul Khoir, located in Grobogan Regency. Despite the madrasah's considerable institutional potential, student academic performance remains suboptimal. To address this issue, the study adopts a qualitative research approach employing a case study design. Data were collected through in-depth interviews with teachers, students, and parents; direct classroom observations; and analysis of academic records. Research instruments included structured interview protocols, observation checklists, and document analysis formats. The findings reveal that the application of the TUS method significantly contributes to increased student motivation, heightened classroom engagement, and overall improvement in academic outcomes. The study also underscores the critical role of institutional and parental support in facilitating the method’s success, while highlighting the need for targeted strategies to address challenges associated with large class sizes to ensure optimal implementation.This study investigates the implementation of the Tutur Uwur Sembur (TUS) instructional method in enhancing student academic achievement at MIS Unggulan Masjid Besar Jabalul Khoir, located in Grobogan Regency. Despite the madrasah's considerable institutional potential, student academic performance remains suboptimal. To address this issue, the study adopts a qualitative research approach employing a case study design. Data were collected through in-depth interviews with teachers, students, and parents; direct classroom observations; and analysis of academic records. Research instruments included structured interview protocols, observation checklists, and document analysis formats. The findings reveal that the application of the TUS method significantly contributes to increased student motivation, heightened classroom engagement, and overall improvement in academic outcomes. The study also underscores the critical role of institutional and parental support in facilitating the method’s success, while highlighting the need for targeted strategies to address challenges associated with large class sizes to ensure optimal implementation.